The beneficial uses of glycerin as an alternative energy source in poultry diets. Issue 1 (1st March 2017) - Arif, M.; Abd El-Hack, M.E.; Hayat, Z.; Sohail, Sh.; Saeed, M.; Alagawany, M.
Abstract : Glycerin or glycerol (C3 H5 (OH)3 ) is one of the most valuable and versatile chemical materials known. The term 'glycerin' refers in general to a commercial solution of glycerol in water of which the main constituent is glycerol. Glycerin is an odourless, colourless, viscous liquid with a sweet taste. It is completely soluble in both alcohol and water. Glycerin is the main co-product derived from biodiesel production. It is produced by a KOH- or NaOH-catalysed transesterification of the triacylglycerols in fat or oil along with an alcohol. Glycerin is an important ingredient for the production of soaps, cosmetics, pharmaceuticals and food. Additionally, glycerin is highly stable under normal storage conditions, practically non-irritating in its different uses, suitable for interactions with other chemical materials and has no any negative environmental impacts. Nowadays, with increasing glycerin production and its availability on the market, many new and novel uses are expected to be developed, particularly as alternative energy source for poultry diets. Furthermore, glycerin plays an essential role in body cellular metabolism. This review paper discusses the various trials using glycerin in poultry diets as an energy source and its effects on different parameters in the birds. Generally, poultry diets, which included glycerin up to 10% in feed, gave positive responses in most of studies, some of which measured apparent metabolisable energy (AMEn). However, more indices need to be determined in further studies in different poultry species.